2011
DOI: 10.1016/j.econedurev.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Student expectations of the financial returns to higher education in the Czech Republic and England: Evidence from business schools

Abstract: In this paper, the shortcut method is used to estimate expected rates of financial returns to higher education in the Czech Republic and a modified version of the method is used to suit the current English system of deferred tuition fees. First year university students were asked to estimate their earnings with and without a university degree at two points in time. The findings show that students perceive higher education to be a profitable investment and that rates of return vary by gender as well as by count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
4
15
1
Order By: Relevance
“…Our results also support previous research from Anchor et al . () suggesting that students perceive education to be a profitable investment.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Our results also support previous research from Anchor et al . () suggesting that students perceive education to be a profitable investment.…”
Section: Discussioncontrasting
confidence: 96%
“…The investment decision rule follows the theory of human capital, which assumes that agents compare the cost of investing in human capital with the expected return in earnings and other benefits, and then equates the two at the margin (Becker, 1975), arguing that students will pursue higher education if benefits marginally exceed costs (investment). A study performed in the Czech Republic and England found that students do, in fact, perceive higher education to be a profitable investment (Anchor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in different countries (e.g. Brunello, Lucifora, and Winter-Ebmer 2004;Webbink and Hartog 2004;Anchor et al 2011) have suggested that, on average, students' expectations are in line with actual graduate premia. On a less positive 808 P. Davies et al note (for human capital theory), Jerrim (2011) presented evidence that, on average, students in England overestimate graduate premia by 15%, whilst Delaney, Harmon, and Redmond (2011) found that students in lower socio-economic groups in Ireland held significantly more pessimistic expectations about graduate premia.…”
Section: Expectations Of Graduate Wagesmentioning
confidence: 91%
“…In most studies of earnings expectations, students have been reported to have an accurate perception of the earnings differential associated with a college degree (Anchor et al 2011;Botelho and Pinto 2004;Dominitz and Manski 1996;Psacharopoulos andSanyal 1981, 1982 and Gordon 1981;Wolter 2000). The link between the perceived rate of return to higher education and the intention to pursue higher studies has been reported to be significant (Hung, Chung, and Ho 2000;Menon 1997Menon , 2008.…”
Section: Economic Social Individual and Institutional Determinantsmentioning
confidence: 99%
“…Despite the widespread acceptance of the human capital model among economists, very few studies have put the underlying assumption to the test as research has focused on the measurement of actual as opposed to expected returns. However, studies of actual rates of return have been criticised for failing to provide corroborating evidence for the human capital model (Anchor et al 2011;Blaug 1976). If a private rate of return is to provide an explanation for the decision of prospective students to pursue higher education, it should ideally be based on the perceptions of these students regarding the costs and benefits of tertiary education.…”
Section: Introductionmentioning
confidence: 99%